P‐type Semiconducting Polymers as Photocathodes: A Comparative Study for Optobioelectronics - Luca Bondi; Camilla Marzuoli; Edgar Gutiérrez‐Fernández; Gabriele Tullii; Jaime Martín; Beatrice Fraboni; David Mecerreyes; Maria Rosa Antognazza; Tobias Cramer (Advanced Electronic Materials, 2023)
Abstract Recent studies have shown that p‐type polymeric semiconductors enable a new type of wireless, optically triggered interface with cells and tissues. Poly(3‐hexylthiophene‐2,5‐diyl) (P3HT) has already been used to create such optobioelectronic interfaces, producing reactive oxygen species and hydrogen peroxide that act as messengers in biological systems to impact cell signaling and proliferation. However, the use of P3HT in biomedical in‐vivo applications is limited as its optical absorption does not match the tissue transparency window. This paper compares the performance of P3HT with two low band‐gap polymers commonly employed in high‐performance organic solar cells, namely Poly[[4,8‐bis[5‐(2‐ethylhexyl)‐2‐thienyl]benzo[1,2‐b:4,5‐b′]dithiophene‐2,6‐diyl]‐2,5‐thiophenediyl[5,7‐bis(2‐ethylhexyl)‐4,8‐dioxo‐4H,8H‐benzo[1,2‐c:4,5‐c′]dithiophene‐1,3‐diyl]] (PBDB‐T) and Poly({4,8‐bis[(2‐ethylhexyl)oxy]benzo[1,2‐b:4,5‐b′]dithiophene‐2,6‐diyl}{3‐fluoro‐2‐[(2‐ethylhexyl)carbonyl]thieno[3,4‐b] thiophenediyl}) (PTB7). Their photogeneration capabilities are quantified in physiological‐like conditions through photocurrent analysis and a hydrogen peroxide assay, finding a superior photocurrent generation and a better H2O2 photogeneration yield in PTB7 as compared to the other two polymers. Spectroscopic and structural investigations are used to compare such differences by comparing their energy levels at the electrochemical interface and their morphologies. Finally, biocompatibility is tested both in dark and illuminated conditions and effective in‐vitro intracellular ROS production is demonstrated. These findings provide insight into the physico‐chemical properties crucial for the development of novel, less invasive, optically operated bioelectronic interfaces.